Adaptive wind-evoked power devices for autonomous motor control applications. Issue 32 (3rd August 2022) - Sha, Wei; Hua, Qilin; Shi, Yuanhong; Wang, Jiangwen; Cui, Xiao; Dong, Zilong; Wang, Bingjun; Niu, Jianan; Hu, Weiguo
Abstract : Wind-evoked power devices based on cantilever-structured GaN HEMTs are demonstrated with large output power modulation of 1.68 × 10 3 W cm −2 and ultrahigh strain sensitivity of 1472, showing great potential in autonomous motor control applications. Abstract : With the explosive development of artificial intelligence, power devices integrated with real-time sensing functions have attracted tremendous attention and will play an important role in intelligent control applications. In this work, a cantilever-structured AlGaN/AlN/GaN high electron mobility transistor integrated with ultrahigh sensitivity and large output power modulation is fabricated through a low-damage anisotropic and isotropic etching process, and achieves excellent electrical performance with a maximal output current of 236 mA mm −1 at a gate bias of 1 V. Due to the facile structure of the cantilever, the device is capable of sensing external stimuli, e.g., gentle wind, and in turn controlling the power output. Significantly, the device exhibits an extraordinarily large output power modulation (Δ P : 1.68 × 10 3 W cm −2 ) under external stimuli in the saturation region, and obtains an ultrahigh strain sensitivity (gauge factor: 1472) under gate voltage in the linear region. Moreover, the wind-evoked mutational behavior of crickets is emulated by the device to demonstrate the capability of autonomous motor control. Such wind-evoked power devices ingeniously coupled with the dynamic piezotronic effect will have great significance in real-time sensing and actuation applications in artificial intelligence, autonomous driving, and aerospace.